Hubungan Pemberian Makanan Pendamping Asi dengan Status Gizi Balita Usia 6-24 Bulan di Desa Sumberbendo Bubulan - Wiwik Utami, Wiwik Utami; Evita Muslima Isnanda Putri, Evita Muslima Isnanda Putri; Oktaviani K, Oktaviani K (Jurnal Penelitian Kesehatan, 2019)
Baby aged 6-24 months need to be given complementary feeding because in need of other nutrients for the development of his body. At this time the baby began to be active in its development. The purpose of this study was to analyze the relationship of ASI Breastfeeding Supplement (CBF) with nutritional status of baby aged 6-24 months in Sumberbendo Village, Bubulan District, Bojonegoro Regency 2018.                           This research design use analytic with cross sectional approach. The population of mothers who have baby under five (6-24 months) in Sumberbendo Village Bubulan District Bojonegoro Regency 2018, the sample of 41 respondents with simple random sampling technique. Variables of CBF were taken with questionnaire and nutritional status of under-five baby taken by observation. Data processed through editing, coding, scoring, tabulating, analyzed by spearman rho statistical test.Result of research from 41 respondents more than half respondents did not give appropriate amount of CBF as many as 26 people (63,41%), more than half of baby less than 21 people (51,22%), and less than half of respondents the provision of CBF did not match as many as 18 respondents (43.9%). It is concluded that there is a relationship of giving of CBF with nutritional status of baby aged 6-24 months in Sumberbendo Bubulan Bojonegoro 2018.Hopefully the respondent increase their understanding about CBF by actively come to Integrated service post and follow counseling about CBF provided by health workers or through print and electronic media available around respondents.